2004
DOI: 10.1074/jbc.m408210200
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Formation of Novel Halogenated 2′-Deoxycytidine

Abstract: A potential role of DNA damage by leukocyte-derived reactive species in carcinogenesis has been suggested. Leukocyte-derived peroxidases, such as myeloperoxidase and eosinophil peroxidase, use hydrogen peroxide and halides (Cl ؊ and Br ؊ ) to generate hypohalous acids (HOCl and HOBr), halogenating intermediates. It has been suggested that these oxidants lead to the formation of halogenated products upon reaction with nucleobases. To verify the consequences of phagocyte-mediated DNA damage at the site of inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 49 publications
1
19
0
1
Order By: Relevance
“…A summary of the various immunostainings can be seen in Table 1. N 4 ,5-diCldC was previously detected by immunohistochemistry in LPS-treated mice (21). The time course of N 4 ,5-diCldC immunostaining was consistent with that of 8-halo-dGs (Table 1).…”
Section: Preparation and Characterization Of Monoclonal Antibody To 8supporting
confidence: 59%
“…A summary of the various immunostainings can be seen in Table 1. N 4 ,5-diCldC was previously detected by immunohistochemistry in LPS-treated mice (21). The time course of N 4 ,5-diCldC immunostaining was consistent with that of 8-halo-dGs (Table 1).…”
Section: Preparation and Characterization Of Monoclonal Antibody To 8supporting
confidence: 59%
“…However, it is now recognized that ONE is more reactive than HNE toward the DNA bases 2Ј-deoxyguanosine (20,22), 2Ј-deoxyadenosine (33,34), and 2Ј-deoxycytidine (35)(36)(37), generating a variety of bulky DNA adducts such as 2-oxo-heptyl-substituted etheno-type adducts. In the present study, we identified ONE as a potential inducer of the p53 response in the human neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorinated nucleosides that might induce genotoxicity have been identified in several tissues and are often discussed with regard to diseases such as inflammation and atherosclerosis. 5,[16][17][18] Taken together, chlorinated nucleosides can be regarded as useful specific biomarkers for HOCl-(and also activated neutrophil-) induced oxidative damage in vivo. In the present study, we examined the effects of several antioxidative compounds on the formation of biomarker Cl-Guo in vitro for the first time using three reaction systems, the HOClinduced chemical reaction, the human MPO-induced enzymatic reaction, and activated human neutrophilinduced cellular reaction system.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) Recently, HOCl was reported to react with nucleic acid bases to form chlorinated and oxidized compounds, e.g., 8-chloroguanosine (Cl-Guo), 8-chloroadenine, 8-chloro-2 0 -deoxyguanosine, 5-chloro-2 0 -deoxycytidine, and 8-oxo-deoxyGuo. [2][3][4][5][6][7][8] In addition, tertiary amines such as nicotine and trimethylamine at physiologically relevant concentrations have been found strongly to enhance Cl-Guo formation mediated by HOCl. 3,9) The G-463A polymorphism of the mpo gene, which reduces the expression of MPO mRNA, has been reported to be associated with reduced risk of lung cancer in cigarette smokers.…”
mentioning
confidence: 99%